Butin Attenuates Arthritis in Complete Freund’s Adjuvant-Treated Arthritic Rats: Possibly Mediated by Its Antioxidant and Anti-Inflammatory Actions - Alzarea, Sami I.; Alasmari, Abdullah F.; Alanazi, Abdullah S.; Alzarea, Abdulaziz I.; Alharbi, Metab; Alshammari, Abdulrahman; Kazmi, Imran; Aljoufi, Fakhria A.; Sayyed, Nadeem; Afzal, Muhammad (Frontiers in Pharmacology, 2022)
The research work was planned to see how effective butin was at preventing arthritis in rats. Adult Wistar rats (200–240 g) were segregated equally into four: Group I (normal) and Group II Complete Freund's Adjuvant (CFA control) were administered orally with 3 ml/kg of 0.5% SCMC (vehicle); Group III and Group IV; were test groups and orally administered 25 and 50 mg/kg of butin. These oral treatments were administered for a total of 21 days. In 21 days treatment schedule, on first day, animals from group I (normal control) were injected single dose of normal saline (0.1 ml) intradermally into one of the hind paw and animals from Group II to IV, were injected CFA (0.1 ml) intradermally into one of the hind paw. During the treatment schedule, volume of hind paw and body weight were recorded at every 7 days intervals and animals were scored for severity arthritic on days 17, 19 and 21. On 22nd day, samples of blood were withdrown by puncturing retro-orbital sinus for analysis of RBC, WBC, haemoglobin, ALT, AST, ALP, PGE2 and cytokenes. After blood withdrawal, animals were killed, paw tissue was obtained for analysis of oxidative stress and antioxidant parameters, as well as histopathological study. Administration of butin to CFA treated animals significantly attenuated CFA-induced inflammatory response, oxidative stress and reversed the histopathological alteration towards normal. According to the findings, butin has anti-inflammatory and anti-arthritic properties in rats with CFA-induced arthritis.